Evolution of circuits regulating pleasure and happiness with the habenula in control. (1st November 2017) - Loonen, Anton J. M.; Ivanova, Svetlana A.
Abstract : The habenula, which in humans is a small nuclear complex within the epithalamus, plays an essential role in regulating the intensity of reward-seeking and adversity-avoiding behavior in all vertebrate ancestors by regulating the activity of ascending midbrain monoaminergic tracts. In lampreys, considered to possess a brain comparable to humans' earliest evolutionary vertebrate ancestor, the activity of the lateral habenula is controlled by a subset of glutamatergic neurons of the animal's pallidum (habenula-projecting globus pallidus) that inhibit reward-seeking behavior when this conduct is not successful enough. The pathophysiological roles of the habenula and habenula-projecting globus pallidus in humans have hardly been studied, which is probably due to insufficient resolution of common neuroimaging techniques. Their dysregulation may, however, play an essential role in the pathogenesis of mood and stress disorders and addiction.